Numerical simulation of the distribution and orientation of steel fibres in SCC. Issue 21 (20th November 2020) - Bao, Chun; Bi, J.H.; Xu, D.; Guan, J.; Cheng, W. X.
Abstract : Due to the combined advantages of steel fibre-reinforced (SFR) concrete and self-compacting concrete (SCC), SFRSCC is considered to present good prospects for engineering applications. As SFRSCC has good flowability and does not require vibration, the casting process directly determines the final distribution and orientation of the steel fibres, which inevitably affects the mechanical properties of SFRSCC. This paper presents a new numerical simulation that uses computational fluid dynamics software Ansys CFX combined with the Matlab program, which can be utilised to simulate the casting procedure of SFRSCC and calculate the distribution and orientation of the fibres in SCC during the casting procedure. To verify the accuracy of the method, the casting procedure of an SFRSCC beam was simulated and the final distribution and orientation of the steel fibres were obtained. The calculation results show good agreement with the experimental results. The influence of the rheological properties of SCC and the length of the steel fibres on the fibre's distribution and orientation was analysed using the new method. The results can be used as reference for SFRSCC experimental research and engineering applications.